Doxycycline-loaded coaxial nanofiber coating of titanium implants enhances osseointegration and inhibits Staphylococcus aureus infection. (5th July 2017) - Song, Wei; Seta, Joseph; Chen, Liang; Bergum, Christopher; Zhou, Zhubin; Kanneganti, Praveen; Kast, Rachel E; Auner, Gregory W; Shen, Ming; Markel, David C; Ren, Weiping; Yu, Xiaowei
Abstract: Few studies have been reported that focus on developing implant surface nanofiber (NF) coating to prevent infection and enhance osseointegration by local drug release. In this study, coaxial doxycycline (Doxy)-doped polycaprolactone/polyvinyl alcohol (PCL/PVA) NFs were directly deposited on a titanium (Ti) implant surface during electrospinning. The interaction of loaded Doxy with both PVA and PCL NFs was characterized by Raman spectroscopy. The bonding strength of Doxy-doped NF coating on Ti implants was confirmed by a stand single-pass scratch test. The improved implant osseointegration by PCL/PVA NF coatings in vivo was confirmed by scanning electron microscopy, histomorphometry and micro computed tomography (μ CT) at 2, 4 and 8 weeks after implantation. The bone contact surface (%) changes of the NF coating group (80%) is significantly higher than that of the no NF group (<5%, p < 0.05). Finally, we demonstrated that a Doxy-doped NF coating effectively inhibited bacterial infection and enhanced osseointegration in an infected ( Staphylococcus aureus ) tibia implantation rat model. Doxy released from NF coating inhibited bacterial growth up to 8 weeks in vivo . The maximal push-in force of the Doxy-NF coating (38 N) is much higher than that of the NF coating group (6.5 N) 8 weeks after implantation ( p < 0.05), which was further confirmed by quantitative histological analysis and μ CT. These findings indicate that coaxial PCL/PVA NF coating doped with Doxy and/or other drugs have great potential in enhancing implant osseointegration and preventing infection.